Potential Leads from Liquorice Against SARS-CoV-2 Main Protease using Molecular Docking Simulation Studies - Sinha, Saurabh K.; Prasad, Satyendra K.; Islam, Md A.; Chaudhary, Sushil K.; Singh, Shashikant; Shakya, Anshul (Combinatorial Chemistry & High Throughput Screening, 2021)
Aim and Objective: At present, the world is facing a global pandemic threat of SARSCoV- 2 or COVID-19 and to date, there are no clinically approved vaccines or antiviral drugs available for the treatment of coronavirus infections. Studies conducted in China recommended the use of liquorice (Glycyrrhiza species), an integral medicinal herb of traditional Chinese medicine, in the deactivation of COVID-19. Therefore, the present investigation was undertaken to identify the leads from the liquorice plant against COVID-19 using molecular docking simulation studies. Materials and Methods: A set of reported bioactive compounds of liquorice were investigated for COVID-19 main protease (Mpro) inhibitory potential. The study was conducted on Autodock vina software using COVID-19 Mpro as a target protein having PDB ID: 6LU7. Results: Out of the total 20 docked compounds, only six compounds showed the best affinity towards the protein target, which included glycyrrhizic acid, isoliquiritin apioside, glyasperin A, liquiritin, 1-methoxyphaseollidin and hedysarimcoumestan B. From the overall observation, glycyrrhizic acid followed by isoliquiritin apioside demonstrated the best affinity towards Mpro representing the binding energy of -8.6 and -7.9 Kcal/mol, respectively. Nevertheless, the other four compounds were also quite comparable with the later one. Conclusion: From the present investigation, we conclude that the compounds having oxane ring and chromenone ring substituted with hydroxyl 3-methylbut-2-enyl group could be the best alternative for the development of new leads from liquorice plant against COVID-19.
Keywords: isoliquiritin apioside